Geography realms, regions, and concepts : study guide - De Blij, Harm J. (John Wiley & Sons, 1997)
This introduction to world regional geography uses fundamental concepts to organize the world around developed and less developed regions, while also providing basic systematic geography. Includes major geographically significant world events through the Spring of 1996.